If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9y + -2 = 0 Reorder the terms: -2 + 3x + 9y = 0 Solving -2 + 3x + 9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 3x + 2 + 9y = 0 + 2 Reorder the terms: -2 + 2 + 3x + 9y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3x + 9y = 0 + 2 3x + 9y = 0 + 2 Combine like terms: 0 + 2 = 2 3x + 9y = 2 Add '-9y' to each side of the equation. 3x + 9y + -9y = 2 + -9y Combine like terms: 9y + -9y = 0 3x + 0 = 2 + -9y 3x = 2 + -9y Divide each side by '3'. x = 0.6666666667 + -3y Simplifying x = 0.6666666667 + -3y
| 3y-2=y-4 | | X^4+12x^2+30=0 | | 2x/3x=1.5 | | (x/3)^2=561 | | (M+5)(m-3)=0 | | z^3+i=0 | | sec^2(x)-1=0 | | 4t^2+15t=3t^2 | | 100*(x/30) | | 0.25(16x+12)+2x=33 | | 19+13p=17p+5 | | 2x^2-21x+5=0 | | 22x^2-21x+55=0 | | 22x^2-21x+5=0 | | X^2-7x+100=0 | | n/4+9=14 | | 13+3x+y=113 | | z^4+4iz^2+8=0 | | -4p+q=-6 | | -3k-5(k+8)=-88 | | 2b-1=6 | | x^2-7=-17 | | (6+7i)-(-7+i)= | | 3(6)+7= | | 12n+2=-47 | | 6(-5x+2)-2x=-84 | | 126p^2-49p-7= | | 79=9w-2 | | 30y^2+23y-14=0 | | -8m-6(m-6)=148 | | 2377960+26=3000000 | | -1(-40)= |